Performance evaluation of the BioSculptor® system as a CAD/CAM tool for transtibial residual limb shape monitoring and generation of socket interface roughness / Nur Afiqah Hamzah - Nur Afiqah , Hamzah (2022)
Multiple factors cause residual limb volume fluctuation, such as amputee's age, health level, and activity level. With the introduction of Computer-aided design and Computeraided manufacturing (CAD/CAM) in the 1980s, the technology has globally changed the fabrication and delivery of prosthetics and orthotics products to amputees. One of the functions of CAD/CAM required is to capture the variation in size and shape of the residual limbs. This thesis was designed to study one of the commercial CAD/CAM systems, the BioSculptor® CAD/CAM system, in capturing transtibial residual limb circumference profiles because there is a limited study done on real subjects for this particular system. Three objectives identified to assess the efficacy and accuracy of the system's components (Bioscanner, Bioshape, and Biomill) and compared the data with the circumferential profiles obtained with the conventional standard tape measurement method. To determine and evaluate the accuracy and the efficacy of the system, active and non-active amputees were recruited to conduct a walking activity for 5 to 25 minutes of walking intervals. Findings showed, both manual and BioSculptor® ‘s Bioscanner measurements gave a general comparable linear pattern. Smallest differences can be seen especially the circumference measurements near the mid-patella tendons. Likewise, pressure- areas of the limb showed only an average of 2.28% differences in measurement between the two techniques. The initial study conducted showed high reliability and repeatability of intra-class correlation (ICC) >0.9. The mean circumferences between the two methods revealed that Bioscanner gave a higher estimation for both amputees. Bioscanner also identified the non-consistence volume change at different locations of the circumference profiles. Both amputees had a significant volume increase at the distal end of the limbs (7.35% change in non-active and 8.83% in active amputees). The residual limb volume's percentage differences were consistent with 2.4% to 9.3%. Additionally, Pearson's coefficient correlation resulted in a high correlation between the digital and manual, ranging from 0.973 to 1 with P<0.05. The advancement of the CAD/CAM system allows users to select the level of surface roughness of the milling products. Surprisingly, there is a lack of study on different surface roughness from milling processes at liner-residual limb interface. Assessment of the effect of different surface roughness from milling processes allowed personalized socket-limb interface based on the amputee's level of activity. To examine the possible effect of different surface roughness on limb shape management, this feature on Biomill was studied. Three surface parameters (arithmetic average (Ra), root mean square roughness (Rq), and tenpoint height (Rz) were chosen, and the results of different surface roughness (STANDARD, FINE, COARSE, and FAST) compared with a liner that had been fabricated conventionally. The Ra values of the conventional liner, 8.43 μm, were determined to be in-between the Ra values of STANDARD and FAST surfaces, which were 8.33 μm and 8.58 μm, respectively. Cutting conditions, such as the feed rate, maximum depth of cut, and speed rate, directly affected the roughness of the surface. By acknowledging the potential of BioSculptor ®, the results of this study would provide guidelines for prosthetists in managing residual limb volume change.